Control Strategies for Multi-Terminal DC Transmission System with Special Parallel Topology - Su, Yun; Li, Shaohua; Li, Binbin; Ma, Xiaoting; Yao, Dongxiao; Zhang, Wang (2020 4th International Conference on HVDC (HVDC), 2020)
With the development of high voltage direct current (HVDC) transmission technology, parallel converters have received increasing attentions. The multi-terminal dc (MTDC) system with parallel connection of converters is particularly advantageous when the transmission is built in stages or when it works under de-icing mode. The simplest MTDC topology with the parallel converters located in the same station is the subject of this paper. The characteristics of four-terminal HVDC system with parallel converters are analyzed. A new cooperation strategy is proposed which rectifiers control dc current, inverters control dc voltage and a per-unit dc current balancing control function applied to avoid an unambiguous operating dc voltage. This cooperation strategy not only simplifies the control system design for the 4-terminal HVDC transmission, retains the independence of the two 2-terminal HVDC systems to the utmost extent, but also any proportion power distribution among the two inverters is achieved. De-paralleling the second converter and paralleling the first converter are of special interest for parallel operation, the methods of doing this are also described. Finally, a case of 4-terminal HVDC system with the special topology validates the control strategies using PSCAD/EMTDC.